Novel S-doped polyaniline@CuCo2O4–carbon composites and optimization of their weight ratios on the basis of their electrochemical activities - Das T.; Verma B. (My University, 2025)
Polyaniline–acetylene black–copper cobaltite-based ternary composites were synthesized with different weight ratios of aniline, acetylene black, and copper cobaltite. Electrochemical testings of all the systems were executed by cyclic voltammetry, charging–discharging, and electrochemical impedance spectroscopy. The optimized weight ratio was found to be 4:1:2 (aniline:acetylene black:copper cobaltite). In three- and two-electrode configurations, polyaniline–acetylene black–copper cobaltite having a weight ratio of 4:1:2 based system showed the highest specific capacitances of 771.03 F/g and 240.11 F/g, respectively, at 5 mV/s. The system had a low charge transfer resistance of 2.8 Ω. It could retain 89.8% of the capacitance after 5000 cycles. At 4:1:2 ratio, the fabricated system exhibited the highest specific power and energy of 125 W/kg and 34.41 Wh/kg, respectively, at 1 mA current. © 2021 Taylor & Francis.